Risk-based decision making - Семке, Ніна Миколаївна; Шляхта, Анастасія Юріївна (My University, 2023)
The article is directed on discovering the essence of managerial decisions and importance of risk assessment for choosing the optimal one. General principles of decision-making in conditions of risk are considered.
Keywords: managerial decision; risk; decision-making; risk theory; risk management; прийняття рішень; оцінка ризику; теорія ризику; ризик; управління ризиками